Periodontal health in children with diabetes mellitus type 1 in Montenegro - Đuričković Mirjana; Ivanović Mirjana; Samardžić Mira; Jovičić Olivera; Popović Zorica (Serbian Medical Society - Dental Section, Belgrade, 2018)
Introduction Separation of instruments in the root canal is one of the challenges in endodontic treatment. More specifically, nickel-titanium (NiTi) rotary instruments usually separate without previous deformation. The aim of this pilot study was to assess the effect of torsional stress on endodontic NiTi rotary instruments separation in simulated clinical conditions. Materials and methods Research was conducted on a sample of 20 human teeth in laboratory conditions. Experimental procedure consisted of determining canal curvatures for each root on digital radiographs and root canal treatment using endodontic NiTi rotary instruments. Out of 20 teeth (60 canals), two groups were formed with similar root canal curvatures (10 pairs of teeth) and instrumented using NiTi rotary instrument with or without torque control. Results Wilcoxon matched pair test showed no statistically significant difference in average number of instruments use with or without torque control (p>0.05). Conclusion Even though there is no statistical significance in instrument separation when instruments were used with or without torque, there is tendency to experience sudden fracture of instruments after work without torsional control even after only few uses in clinical work.